Cold tolerance identification of nine Rosa L. materials and expression patterns of genes related to cold tolerance in Rosa hybrida - Wang, Hongli; Cheng, Xi; Shi, Qiyu; Xu, Jie; Chen, Dongliang; Luo, Chang; Liu, Hua; Cao, Li; Huang, Conglin (Frontiers in Plant Science, 2023)
Members of the Rosa genus have a high ornamental value, but their cultivation area is limited by their sensitivity to cold temperatures. The aim of this study was to evaluate the cold tolerance of a range of Rosa materials, and then determine which genes are related to cold tolerance. Nine Rosa materials were subjected to a cold treatment, and the most cold-tolerant materials were identified as those that showed the lowest levels of electrolyte leakage and the best recovery after 30 d of growth. The most cold-tolerant materials were Rosa hybrida, Rosa rugosa ‘Pingyin 12’, and R. rugosa var. To identify genes related to cold tolerance, R. hybrida was treated at −15 °C for 10 min, and leaves collected before and after this treatment were collected for RNA-Seq analyses. In total, 204 significantly differentially expressed genes (DEGs) were identified, of which 88 were significantly up-regulated and 116 were significantly down-regulated under cold conditions. Gene Ontology classification and Kyoto Encyclopedia of Genes and Genomes pathway analyses showed that the DEGs were enriched in 57 pathways, especially starch and sucrose metabolism, phenylpropane biosynthesis, MAPK signaling, fructose and mannose metabolism, and oxidative phosphorylation. The transcript profiles of four DEGs (POD17, NDUFA9, PMA1, and β-Amy1) in R. hybrida were determined by qRT-PCR at 0 h, 1 h, 2 h, and 3 h at −15 °C. PMA1, which is related to H+ ATPase activity, was continuously up-regulated, but the transcript levels of POD17, NDUFA9, and β-Amy1 fluctuated during the freezing treatment. These results lay the foundation for further research on the cold tolerance mechanism of Rosa L. plants and the breeding of new, cold-tolerant varieties.